2014
DOI: 10.6000/1929-4247.2014.03.02.4
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Dehydration and Malnutrition to the Mortality of Children 0-59 Month of Age in a Senegalese Pediatric Hospital

Abstract: In-hospital mortality is an indicator of the quality of care. We analyzed the mortality of under five years children of Pediatric ward of Aristide Le Dantec teaching hospital to update our data, after an previous study conducted ten years earlier. Methods: This was a retrospective study involving children 0-59 months of age, hospitalized from January 1, 2012 to December 31, 2012. For each child, nutritional status was assessed according to 2006 World Health Organization growth standards; clinical and biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…The hospital mortality found in this study seems low compared to those found in Dakar (10%), Ivory Coast (10.64%) and Togo (15.6%) [3,4,5] . This mortality was higher for the 1 to 12 month age group (68.18%) with a statistically significant link (p<0.001 and 0R=5.33).…”
Section: ) (See Table)contrasting
confidence: 74%
See 2 more Smart Citations
“…The hospital mortality found in this study seems low compared to those found in Dakar (10%), Ivory Coast (10.64%) and Togo (15.6%) [3,4,5] . This mortality was higher for the 1 to 12 month age group (68.18%) with a statistically significant link (p<0.001 and 0R=5.33).…”
Section: ) (See Table)contrasting
confidence: 74%
“…Acute malnutrition was statistically associated with death with p=0.007 and OR=3.37. Seck and Sylla found in their studies that malnutrition was the main factor in mortality in children less than 5 years of age (31%) [3,7] , whereas Asse et al in Ivory Coast found that malnutrition accounted for only 1% of deaths [4] . Severe acute malnutrition, through its complications, is still a major public health problem and is an independent risk factor for death in hospitalized Senegalese children [3] .…”
Section: ) (See Table)mentioning
confidence: 99%
See 1 more Smart Citation